Perspektif Mahasiswa Fisika Kelas Kimia Umum terhadap Rehidrasi melalui Minuman Elektrolit Alami dalam Program MBG - Dimas Ridho; Gilbert Situmorang; Khalishah Husna Simanjuntak; Soha Khairunnisa Siregar; Raja Khairani (Oxygenius: Journal Of Chemistry Education, 2026)
While national nutritional programs are increasingly promoted, university students' awareness of science-based rehydration remains largely overlooked. This paper explores how General Chemistry students at the State University of Medan (UNIMED) perceive rehydration and bodily ion balance. Crucially, it examines these concepts through the lens of natural electrolyte beverages meant to supplement the national Free Nutritious Food Program (MBG). To achieve this, we gathered data from 41 active chemistry students using a quantitative descriptive design via voluntary convenience sampling. The research instrument consisted of a 5-point Likert questionnaire (20 items) covering knowledge, attitude, and behavior dimensions, demonstrating sound validity (r-calculated: 0.700–0.954) and exceptional reliability (α = 0.983). Our descriptive metrics highlight strong baselines across knowledge (mean: 4.57) and attitude (mean: 4.59), with behavior trailing slightly at 4.43—all settling comfortably within the good-to-excellent bracket. Even so, the data uncovers a clear knowledge-behavior gap: roughly 31.7% of surveyed students still bypass natural electrolyte drinks after working out. Ultimately, this proves that a solid conceptual grasp and positive outlook on ion balance do not automatically spark consistent, real-world healthy habits. This study recommends integrating contextual learning and practical sessions on making natural electrolyte drinks into General Chemistry courses as an effort to support health literacy and strengthen nutrition education in the MBG Program.